An Experimental Study to Strengthen Students' Comprehension of Informational Texts: Is Teaching for Transfer Important?. Issue 2 (10th May 2022) - Patton, Samuel Allen; Fuchs, Douglas; Hendricks, Emma L.; Pennell, Annie J.; Walsh, Meagan E.; Fuchs, Lynn S.; Tracy, Wen Zhang; Haga, Loulee Yen
Abstract: Reading nonfiction texts with understanding is important to school success, yet many students struggle to do so. This randomized controlled trial extends previous research by contrasting an earlier iteration of a comprehension tutoring program (Comp) against a variant with strategies for transferring learning (Comp+Transfer). Participants were 189 fourth and fifth graders with weak reading comprehension. To evaluate their efficacy, we used commercially developed far‐transfer measures and experimenter‐made near‐ and mid‐transfer measures of reading comprehension. In contrast to controls, students in both programs significantly improved their understanding of near‐transfer passages. Additionally, students in Comp+Transfer improved performance on mid‐transfer passages. These findings suggest the value of teaching for transfer and the importance of measuring program efficacy with researcher‐made tests alongside commercial tests.